Analisis Budaya Komunikasi Organisasi Di Tim Marketing Central Jawa Timur Park Dalam Meningkatkan Efektivitas Kerja Tim - Abdullah, Muhammad Ghatfan; Nasvian, Moch. Fuad (LPPM Universitas Dharma Andalas, 2025)
. Organizational communication culture plays a vital role in shaping working relationships within a team. This study aims to analyze the organizational communication culture in the Marketing Central (MC) Team of Jawa Timur Park (JTP), focusing on the hierarchical and participatory practices applied in daily work routines. Using a qualitative approach and semi-structured interviews, the researcher involved 14 active informants. The findings show that communication in MC JTP follows a top-down managerial structure, complemented by informal participatory communication among team members. Although this practice reflects flexible structuring, it does not fully align with dialogic communication principles. Communication barriers such as limited access to information and managerial dominance still occur but are generally resolved through direct dialogue or internal mediation. This research highlights that the communication culture in MC JTP is built not only on formal structures but also through symbolic daily interactions, as explained by Deetz and Geertz & Pacanowsky. The findings suggest that balancing control with flexibility can maintain work effectiveness, though improvements in open forums and evaluations are needed to enhance full member participation.